Whitlow, felon and paronychia - a clinical review of superficial hand infections - Mikołaj Domański; Natalia Wierzejska; Barbara Kopczyńska; Oliwia Czyżniewska; Karolina Czupryńska; Karina Otręba; Julia Szałajska; Maria Wojcieszek (Nicolaus Copernicus University in Toruń, 2024)
Paronychia, felon and herpetic whitlow are common superficial hand infections. Although having similarities there are many differences between clinical presentation and treatment. Paronychia can present as acute and chronic condition. Treatment options varies from medical to surgical therapy. Formed abscesses may require drainage and possible antibiotic course. Herpetic whitlow is rare manifestation of hand infection with unique treatment options. Chronic infections differs in etiology and clinical presentation and need specialized treatment. Role of noninfectious causes should always be considered, including malignancy if no adequate treatment response is gained.  Making correct diagnosis, followed by adequate treatment will prevent huge range of complications. Article reviews common hand infections, presentation, diagnosis and treatment strategies.